Role of FPOs in strengthening millet value chain - Sangappa; Rafi, D (Indian Farming, 2023)
In India, majority of the farmers are small and marginal farmers involved in agriculture and allied activities for their livelihood. To help small and marginal farmers, Government of India has initiated a concept of Farmer Producer Organization (FPO). Farmer Producer Organizations of Indian Institute of Millets Research (IIMR) are playing a major role in bringing farmers together by helping them in identifying markets, creating a unique platform for collective purchase of inputs and marketing of produce in bulk, thereby eliminating or reducing the number of intermediaries in the existing supply channel.